15th International Conference on Turbochargers and Turbocharging PROCEEDINGS OF THE 15TH INTERNATIONAL CONFERENCE ON TURBOCHARGERS AND TURBOCHARGING (TWICKENHAM, LONDON, 16-17 MAY 2023) - Institution of Mechanical Engineers (Taylor & Francis, 2023)
The Institution's International Conference on Turbochargers and Turbocharging (Twickenham, London, UK, 16-17 May 2023) returns to address the latest advances, research and developments in turbocharging system designs and boosting solutions. This volume presents a peer-reviewed collection of papers which will address current and novel turbocharging system choices and components with a renewed emphasis to address the challenges posed by emission regulations and market trends. The latest developments leading to enhanced performance and efficiency, increased durability and reduced emissions in line with meeting Net-Zero and global emissions targets. Topics include: Air management in powertrains: conventional, hybrids, fuel cells and novel configurations Alternate fuels and their needs in boosting (e.g. hydrogen, synthetic fuels) Electrification of turbochargers, compressors, and exhaust turbines Simulation and testing techniques, data analytics, including AI and digital twins Thermal management, waste heat recovery and expanders Turbomachinery aerodynamic: novel compressors & turbines and multi-stage systems. Component fatigue life, bearing design, rotor-dynamics and durability prediction Mechatronics, control, sensors and power electronics High speed turbomachinery in propulsion and power systems Future Legislation needs for thermal propulsion systems